just work your way from the inside:
-(2x-(5x+2)-2+(2x+7)
-(2x-5x-2-2+2x+7
Oops: You have an extra left parenthesis.
Fix that and change the appropriate signs to continue on...
need help with this problem. -(2x-(5x+2)-2+(2x+7)
2 answers
You have mismatched sets of brackets, that is,
the number of right-sided brackets is not the same as left-sided brackets. I will assume there is one final at the end.
-(2x-(5x+2)-2+(2x+7) )
= -(2x-5x-2-2+2x+7 )
= -(-x + 3)
= x-3
the number of right-sided brackets is not the same as left-sided brackets. I will assume there is one final at the end.
-(2x-(5x+2)-2+(2x+7) )
= -(2x-5x-2-2+2x+7 )
= -(-x + 3)
= x-3